HUBUNGAN SELF-ESTEEM DENGAN TNGKAT KECEMASAN ATLET RENANG EKSTRAKULIKULER SDN PARAKANMUNCANG II - Mizan Auliyarakhman Firdaus Banu; Dinar Dinangsit; Rizal Ahmad Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Anxienty can adversely affect an individual’s abilities, particularly in athletes by impairing motor skill and preventing them from performing at their optimal level. To effectively manage anxiety, it is crucial to strengthen psychological aspects such as self-esteem. Individuals with high level of slef-esteem tend to be more capable of controlling and coping with anxiety. This study aims to examine the relationship between self-esteem and anxiety levels in extracurricular swimming athlets at SDN Parakanmuncang II. This research employed a quantitative correlational design with a cross-sectional approach. The sample consisted of 30 athletes selected through total sampling. Data were collected using the Rosenberg Self-Esteem Scale (RSES), and the South African Depression and Anxiety Group (SADAG) anxiety questionnaire. The Spearman rank correlation test was untilized for statistical analysis. The results revealed a significant negative correlation between self-esteem and anxiety levels, with a strong inverse relationship. These findings support the study’s hypothesis and highlight the importance of fostering self-esteem to reduce anxiety among student athlets.